Crossed Corticospinal Facilitation Between Arm and Trunk Muscles Correlates With Trunk Control After Spinal Cord Injury - Chiou, Shin-Yi; Strutton, Paul H. (Frontiers in Human Neuroscience, 2020)
Objective: To investigate whether crossed corticospinal facilitation between arm and trunk muscles is preserved following spinal cord injury (SCI) and to elucidate these neural interactions for postural control during functional arm movements. Methods: Using transcranial magnetic stimulation (TMS) in 22 subjects with incomplete SCI motor evoked potentials (MEPs) in the erector spinae (ES) muscle were examined when the contralateral arm was at rest or performed 20% of maximal voluntary contraction (MVC) of biceps brachii (BB) or triceps brachii (TB). Trunk function was assessed with rapid shoulder flexion and forward reaching tasks. Results: MEP amplitudes in ES were increased during elbow flexion in some subjects and this facilitatory effect was more prominent in subjects with thoracic SCI than in the subjects with cervical SCI. Those who showed the increased MEPs during elbow flexion had faster reaction times and quicker anticipatory postural adjustments of the trunk in the rapid shoulder flexion task. Onset of EMG activity in ES during the rapid shoulder flexion task correlated with the trunk excursion in forward reaching. Conclusions: Our findings demonstrate that crossed corticospinal facilitation in the trunk muscles can be preserved after SCI and is reflected in trunk control during functional arm movements.